# Yahoo奇摩 網頁搜尋

1. ### Time expressions

每小時15分 = every hour at quarter past 每小時30分 = every hour at half past 每小時45分 = every hour at quarter to 每小時踏正 = on the hour every hour 2013-06-15 20:38:09 補充： 每小時10分 = every hour at ten past 每小時40分 = every hour at twenty to .

2. ### Fractional Expressions

1.6/(x^2-9)-2/(x^2-1) 2.2/(a^2+4a+3)-2/(a^2+6a+8) 3.2/(a^2-1)-2(a^4+2a^2+6)/(a^6+a^4+a^2+1)

分類：科學及數學 > 數學 2008年02月24日

3. ### Funny expressions

01: because snake has no leg 02:caught him red-handed 姐係the farmer當場抓到個THIEF AS BUSY AS A BEE IS A METAPHOR Bee is always busy (bcoz 要採蜜) which means that person...

分類：社會及文化 > 語言 2011年09月19日

4. ### Factorial expression

Γ(z)Γ(1-z)=π/sin(πz)Part 1: Γ(z)= 2∫[0~∞] x^(2z-1)exp(-x^2) dx Γ(z) = ∫[0~∞] t^(z-1)exp(-t) dx (Let t=x^2) = 2∫[0~∞] x^(2z-1)exp(-x^2) dx Part 2: Γ(z)Γ(1-z)= 2∫[0~π/2] tan^(1-2z) dθ Γ(z)Γ(1-z) ={2∫[0~∞] x^(2z-1)exp(-x^2) dx}{2...

分類：科學及數學 > 數學 2010年12月29日

5. ### Binomial expression

(1-y+3y^2)^3 =[1-y(1+3y)]^3 =(1)(1)-3(y)(1+3y)+3(y^2)(1+3y)^2-(y^3)(1+3y)^3 =1-3y+12y^2-19y^3+....// 2008-07-03 16:07:08 補充： (1-y+3y^2-12y^3)^3 =1-3y+12y^2-55y^3+....// 2008-07-07 19:08:26 補充： (1-y+3y^2-12y^3)^3 =-1728y^9+1296y^8-756y^7+675y^6-279y^5+108y^4-55y^3+12y^2-3y+1

分類：科學及數學 > 數學 2008年07月12日

6. ### formulaic expressions

It has been a long time since we last met./ I have not seen you for a long time. How are you? I miss you very much. I haven't written any letter to you since the summer holidays. How are you getting on? I...

分類：社會及文化 > 語言 2010年05月22日

7. ### expressions +ing

Don't waste time surfing the net. (use verb+ing form because you are surfing the net now. If you are not surfing the net now, then you can use [to + verb] infinitive)

分類：社會及文化 > 語言 2008年01月10日

8. ### expression

It should be restricted. Certain human experiments may harm the society. For example: the Japanese did to the Manchu people of Chinese. They tested how bomb explosion can affect human flesh, reattach limbs...

分類：社會及文化 > 語言 2009年01月10日

9. ### Expression For 'a'

Find An Expression For 'a' if a^b=b^c a=b^(c/b)

分類：科學及數學 > 數學 2013年08月28日

10. ### Factorize this expression ...

4(a-b)^3-12(b-a)^2 = 4(a-b)^3-12(a-b)^2 = 4 (a-b)^2 [(a-b) -3] = 4(a - b - 3) (a - b)^2 2006-11-21 10:42:49 補充： (a-b)^2 = (b-a)^2we can take out 4 (a-b)^2 at the same timeThe above solution can finish the question with the fewest steps

分類：科學及數學 > 數學 2006年11月25日

1. ### 相關詞

 expression